An evanescent field absorption gas sensor at mid-IR 3.39 μm wavelength. Issue 18 (11th October 2017) - Butt, M. A.; Degtyarev, S. A.; Khonina, S. N.; Kazanskiy, N. L.
Abstract: Trace gases such as H2 O, CO, CO2, NO, N2 O, NO2 and CH4 strongly absorb in the mid-IR (>2.5 μm) spectral region due to their fundamental rotational and vibrational transitions. CH4 gas is relatively non-toxic, however, it is extremely explosive when mixed with other chemicals in levels as low as 5% and it can cause death by asphyxiation. In this work, we propose a silicon strip waveguide at 3.39 μm for CH4 gas sensing based on the evanescent field absorption. These waveguides can provide the highest evanescent field ratio (EFR)>55% with adequate dimensions. Moreover, EFR and sensitivity of the sensor are highly dependent on the length of the waveguide up to a certain limit. Therefore, it is always a compromise between the length of the waveguide and EFR in order to obtain greater sensitivity.